Separable Lindenstrauss spaces whose duals do not contain weak* closed convex unbounded sets having the AFPP (2023)
We characterize all separable L1-preduals X for which every weak* closed convex unbounded set in X* lacks the approximate fixed point property for nonexpansive mappings. Our result improves and completes the main theorem in [4], where this property was studied for C(α) and C0(α) spaces with α an infinite countable ordinal as well as for ℓ1-predual hyperplanes in c.